2013
DOI: 10.1177/0883073813477203
|View full text |Cite
|
Sign up to set email alerts
|

One Novel and One Recurrent Mutation in IGHMBP2 Gene, Causing Severe Spinal Muscular Atrophy Respiratory Distress 1 With Onset Soon After Birth

Abstract: A family with 2 siblings with severe spinal muscular atrophy with respiratory distress 1 (SMARD1) was genetically proved to be caused by mutations in IGHMBP2 gene. Both patients developed progressive muscular weakness and respiratory distress and died before 6 months of age. One novel deletion, c.780delG;p.(Gln260Hisfs*24), inherited from the father and a nonsense mutation, c.1488C>A;p.(Cys496*), inherited from the mother were detected. An attempt was made to correlate the genetic-clinical data available in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Among the 52 literature articles screened (Supplementary Table S1) (Robison et al, 1998;Grohmann et al, 2001Grohmann et al, , 2003Guenther et al, 2004Guenther et al, , 2007Maystadt et al, 2004;Giannini et al, 2006;Wong et al, 2006;Joseph et al, 2009;AlSaman and Tomoum, 2010;Baughn et al, 2011;Pierson et al, 2011;Chalancon et al, 2012;Eckart et al, 2012;Majid et al, 2012;Messina et al, 2012;Gitiaux et al, 2013;Blaschek et al, 2014;Cottenie et al, 2014;Jedrzejowska et al, 2014;Lin et al, 2014;Litvinenko et al, 2014;Hamilton et al, 2015;Han et al, 2015;Wagner et al, 2015;Lingappa et al, 2016;Luan et al, 2016;Pedurupillay et al, 2016;San et al, 2016;Dohrn et al, 2017;Liu et al, 2017;Yuan et al, 2017;Zhang et al, 2017;Habibi et al, 2018;Kulshrestha et al, 2018;Tomaselli et al, 2018;Wu et al, 2018;Cassini et al, 2019;Kim et al, 2019;Yasui et al, 2019;Cortese et al, 2020;…”
Section: Resultsmentioning
confidence: 99%
“…Among the 52 literature articles screened (Supplementary Table S1) (Robison et al, 1998;Grohmann et al, 2001Grohmann et al, , 2003Guenther et al, 2004Guenther et al, , 2007Maystadt et al, 2004;Giannini et al, 2006;Wong et al, 2006;Joseph et al, 2009;AlSaman and Tomoum, 2010;Baughn et al, 2011;Pierson et al, 2011;Chalancon et al, 2012;Eckart et al, 2012;Majid et al, 2012;Messina et al, 2012;Gitiaux et al, 2013;Blaschek et al, 2014;Cottenie et al, 2014;Jedrzejowska et al, 2014;Lin et al, 2014;Litvinenko et al, 2014;Hamilton et al, 2015;Han et al, 2015;Wagner et al, 2015;Lingappa et al, 2016;Luan et al, 2016;Pedurupillay et al, 2016;San et al, 2016;Dohrn et al, 2017;Liu et al, 2017;Yuan et al, 2017;Zhang et al, 2017;Habibi et al, 2018;Kulshrestha et al, 2018;Tomaselli et al, 2018;Wu et al, 2018;Cassini et al, 2019;Kim et al, 2019;Yasui et al, 2019;Cortese et al, 2020;…”
Section: Resultsmentioning
confidence: 99%
“…The hypothesis that a greater reduction in IGHMBP2 corresponds to a more severe SMARD1 clinical phenotype has been addressed in the literature. For instance, Litvinenko et al reported in 2013 that a total absence of IGHMBP2 protein is correlated with more severe SMARD1 [63]. The same was suggested in 2014 by Cottenie and her group, who demonstrated that IGHMBP2 mutations are responsible for some cases of CMT2 and suggested that IGHMBP2 mutations that have a greater impact on IGHMBP2 protein levels are responsible for SMARD1, while milder mutations are responsible for CMT2, which is characterized by lower clinical severity [19].…”
Section: Genetics Of Smard1mentioning
confidence: 87%
“…This phenomenon could be related with physic-chemical alterations of the protein, which forms high molecular weight aggregates that are quickly degraded [2]. The total absence of IGHMBP2 enzymatic activity is generally associated with a more severe form of SMARD1 [32]. However some exception to this rule can exist.…”
Section: Genetic Background Of Smard1mentioning
confidence: 96%